Pablo de la Llave: un ilustrado entre dos siglos y dos mundos - Huerta Jaramillo, Ana María (1999)
Pablo de La Llave was an illustrated priest who lived during the end of the 18th century until the beginning of the 19th. His scientific formation was produced in two continents, Europe and America. He was a naturalist and worked as a zoologist, botanist, entomologist and politician. He was related to the most important intellectual people of his time, for example José María Mociño and Geoffroy Saint-Hilaire. De La Llave and Mociño made the classification of birds of the Real Gabinete de Historia Natural of Madrid. Among other activities, De La Llave also cataloged different kinds of vegetables and insects from Europe and America. He also gave impetus to some publications, both in Spain and in Mexico. This issues are nowadays sources of information necessary to those who work in the history of the botanic field. De La Llave established scientific relations with Antonio de la Cal y Bracho, a botanist and apothecary in México, who was born in Burgos and developed his researchs in the Real Hospital de San Pedro in Puebla city. Both of them, De La Llave and Cal, studied and classified differents kinds of nature.